Los indios y las redes clientelares paternalismo, negociación y subordinación en el valle del río Cauca, 1680-1780 - Cuevas Arenas, Héctor (Universidad Santiago de Cali, 2020)
This article studies the dynamics of Indian individuals and collectives participation in clienteles in specific spaces and times, concretely in their vertical dimension, that is, as subordinate agents with priests, encomenderos and neighbors. This, as an example of the dialectic and diachronic of the indigenous agency, together with its mechanisms of adaptation and negotiation with other actors and justice. It seeks to understand clientelism as an expression of the political culture of the time and its changes in two periods: one, from 1680 to 1738 that coincides with the encomienda and another, until 1780, which was within a framework of a recomposition of regional powers.